2018
DOI: 10.1038/s41467-018-05402-2
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic targets Pin1 and cooperates with retinoic acid to inhibit cancer-driving pathways and tumor-initiating cells

Abstract: Arsenic trioxide (ATO) and all-trans retinoic acid (ATRA) combination safely cures fatal acute promyelocytic leukemia, but their mechanisms of action and efficacy are not fully understood. ATRA inhibits leukemia, breast, and liver cancer by targeting isomerase Pin1, a master regulator of oncogenic signaling networks. Here we show that ATO targets Pin1 and cooperates with ATRA to exert potent anticancer activity. ATO inhibits and degrades Pin1, and suppresses its oncogenic function by noncovalent binding to Pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 82 publications
(214 reference statements)
5
146
0
Order By: Relevance
“…Furthermore, the sulfonyl oxygens mediate hydrogen bonds to the backbone amide of Gln131, and the imidazole NH of His157. These hydrogen bonds are analogous to those formed between Pin1 and arsenic trioxide 38 (Supp. Fig.…”
Section: Sulfopin Potently Binds and Inhibits Pin1mentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, the sulfonyl oxygens mediate hydrogen bonds to the backbone amide of Gln131, and the imidazole NH of His157. These hydrogen bonds are analogous to those formed between Pin1 and arsenic trioxide 38 (Supp. Fig.…”
Section: Sulfopin Potently Binds and Inhibits Pin1mentioning
confidence: 79%
“…Indeed, compounds that inhibit Pin1, such as juglone 36 , all-trans retinoic acid (ATRA) 37 , arsenic trioxide (ATO) 38 and KPT-6566 39 , exhibit anti-cancer activity and have been used to investigate the role of Pin1 in oncogenesis. Nevertheless, these compounds have been shown to lack specificity and/or cell permeability thus making them unreliable as tools to interrogate the consequences of pharmacological inhibition of Pin1 in vivo [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Pin1 can activate multiple cancer-promoting pathways in human cancers [54]. Several Pin1 inhibitors have been identified to date, such as juglone, PiB and ATRA; these inhibitors have both covalent and non-covalent mechanisms of action [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the PIN1 inhibitors are non-covalent PIN1 inhibitors (e.g., PiB, ATRA, ATO, and API-1). Similar to covalent PIN1 inhibitor, non-covalent PIN1 inhibitor also directly binds to the PIN1 PPIase domain, but inhibits PIN1 activity in a competitive manner (Uchida et al, 2003;Wei et al, 2015;Kozono et al, 2018;Pu et al, 2018). However, there are limitations of these PIN1 inhibitors that restrict their clinical application ( Table 3).…”
Section: Development Of Pin1 Inhibitors For Hcc Treatmentsmentioning
confidence: 99%
“…The anti-cancer effect of ATO mainly depends on its ability to induce ubiquitin-dependent proteasomal degradation of various oncogenic proteins, including promyelocytic leukemia-retinoic acid receptor-alpha (PML-RARA) in APL, cyclin D1 in mantle cell lymphoma, and nucleophosminanaplastic lymphoma kinase (NPM-ALK) in anaplastic large cell lymphoma (Shao et al, 1998;Lo and Kwong, 2014;Piao et al, 2017). Through the proteasome pathway, ATO has also been found to induce PIN1 degradation by directly binding to the PIN1 PPIase domain (Kozono et al, 2018). ATO-induced PIN1 degradation results in the suppression of multiple PIN1mediated oncogenic pathways and inhibition of breast cancer cell proliferation in vitro and in vivo.…”
Section: Pin1 and Atomentioning
confidence: 99%